Kapasitas Guru Profesional Di Pendidikan Dasar Islam - Prastowo, Andi (Literasi: Jurnal Ilmu Pendidikan, 2013)
Professional needs of teachers in the Elementary School is a very huge necessity, moreover government assigned National Standards of Education and teacher certification. However, the various efforts made by the government has been not significant results yet although the government's efforts can’t be considered pity. The one reason is because it still seems unclear concept of professional teachers in Elementary School. From the results of this literature study, it was found that the required professional teachers especially in Elementary School must have a capacity of four, namely intellectual and research, spiritual, moral and ethic capacity, and last is emotional capacity. Keywords: quality of education, certification, capacity, professional teachers.